Mengukur Ketahanan Ekonomi Sulawesi Tenggara 2017-2023 - Putri, Novia Dwi Kumala; Wulandari, Dyah Kusumaning Ayu; Setiawan, Iman (Seminar Nasional Official Statistics, 2025)
Economic resilience emerged as a key concern for the government facing shocks from the COVID-19 pandemic and the Russia-Ukraine conflict. The economic resilience refers to a region's ability to bounce back quickly from economic challenges. Although Southeast Sulawesi's economic growth improved, the percentage of poor people increased during 2020-2023, signaling false economic resilience. The objective of this study is to assess the degree of economic resilience of Southeast Sulawesi through the Index of Economic Resilience (IKE) formed using factor analysis of panel data in 17 districts from 2017-2023. The results indicate the formation of three dimensions that make up the IKE, namely human capabilities, economic transformation, and income inequality. The average IKE value of the Southeast Sulawesi ranged from 0,29 to 0,40, indicating a gradual improvement in economic resilience. However, there is still an imbalance in the IKE between regions. Industrial downstreaming is one of the policies that should be considered to optimize economic resilience.